2008
DOI: 10.1097/fpc.0b013e32830e1e16
|View full text |Cite
|
Sign up to set email alerts
|

Role of cytochrome P450 2C8 and 2J2 genotypes in calcineurin inhibitor-induced chronic kidney disease

Abstract: Objectives-The calcineurin inhibitors (CNIs) cyclosporine A (CsA) and tacrolimus (Tac) help prevent allograft rejection but are associated with nephrotoxicity. Cytochrome P450 2C8 (CYP2C8) and CYP2J2 are polymorphic enzymes expressed in the kidney that metabolize arachidonic acid (AA) to epoxyeicosatrienoic acids, promoting kidney homeostasis. This study examined the association between CNI-induced nephrotoxicity in liver transplant patients and CYP2C8 and CYP2J2 polymorphisms.Methods-Liver transplantation pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 38 publications
(43 reference statements)
1
50
1
Order By: Relevance
“…Initial in vitro studies for CYP2C8*3 suggested a lower activity, 31,32 but more recent studies in healthy volunteers have repeatedly demonstrated an increased metabolizing capacity for this allele. [33][34][35][36] In contrast, CYP2C8 haplotype C 35,41 and CYP3A5*3 37 confer a reduced activity. As the polymorphisms conferring a low metabolizing capacity were associated with protection, whereas the allele with increased activity showed a higher neurotoxicity (Figure 2), and the effects of these polymorphisms were independent, we incorporated them in a single prediction model (risk alleles: rs11572080 A, rs1113129 G and rs776746 G; Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Initial in vitro studies for CYP2C8*3 suggested a lower activity, 31,32 but more recent studies in healthy volunteers have repeatedly demonstrated an increased metabolizing capacity for this allele. [33][34][35][36] In contrast, CYP2C8 haplotype C 35,41 and CYP3A5*3 37 confer a reduced activity. As the polymorphisms conferring a low metabolizing capacity were associated with protection, whereas the allele with increased activity showed a higher neurotoxicity (Figure 2), and the effects of these polymorphisms were independent, we incorporated them in a single prediction model (risk alleles: rs11572080 A, rs1113129 G and rs776746 G; Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Those who once had acute rejection and the relapse of the primeval disease were excluded. Among all the transplantation recipients, we divided those recipients into stable group (SCr b 1.6 mg/dl) and renal dysfunction group (SCr ≥ 1.6 mg/dl) [10,11]. 27 age and gender-matched healthy subjects were included as normal controls.…”
Section: Patientsmentioning
confidence: 99%
“…EETs help to maintain blood pressure, are involved in tubular reabsorption of water and sodium transport, protect against inflammation, and the maintenance of vascular smooth muscle tone. [73][74][75] Smith et al [76] found that patients carrying one or more CY2C8*3 variant alleles have a higher risk of developing CNI-induced nephrotoxicity after liver transplantation. Possibly, decreased production of EETs in patients with the variant CYP2C8*3 allele may reduce the capacity of their kidneys to counter the vasoconstrictive effects of CNIs.…”
Section: Nephrotoxicitymentioning
confidence: 99%